2006
DOI: 10.1007/s10517-006-0408-5
|View full text |Cite
|
Sign up to set email alerts
|

Stromal regulation of hemopoietic stem cells in long-term human bone marrow tissue cultures under the effect of parathyroid hormone

Abstract: We studied the interaction between different categories of hemopoietic precursors with parathyroid hormone-activated stromal microenvironment. Improved survival of early precursors capable long-term hemopoiesis maintenance and increased number of later short-term repopulating precursors was demonstrated on the model of co-culturing of human bone marrow cells on a layer of adherent cells of long-term bone marrow cultures treated with parathyroid hormone. These changes correlate with increased expression of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…PTH is known to activate osteoblasts in the niches where its presence improves the maintenance of hematopoiesis and adhesion of HSC to the stromal cells. 45 Accordingly, it was hypothesized that PTH may affect gene expression in LTBMC from AA patients or donors after treatment with AA serum. Our results show that the addition of PTH to these cultures normalized the pathological alterations.…”
Section: Discussionmentioning
confidence: 99%
“…PTH is known to activate osteoblasts in the niches where its presence improves the maintenance of hematopoiesis and adhesion of HSC to the stromal cells. 45 Accordingly, it was hypothesized that PTH may affect gene expression in LTBMC from AA patients or donors after treatment with AA serum. Our results show that the addition of PTH to these cultures normalized the pathological alterations.…”
Section: Discussionmentioning
confidence: 99%
“…PTH is an approved polypeptide for the treatment of osteoporosis because it stimulates bone formation that results in increased bone mineral density with additional known effects on hematopoiesis. 23 Indeed, PTH can directly stimulate the proliferation and survival of HSPC, but it also partially exerts its effects through the OB 24 by increasing the production of Jagged 1 in OB, which in turn activates Notch receptors on nearby HSPC. Moreover, PTH has also been shown to act through the insulin-like growth factor pathway, which is specifically upregulated in OB, but not MSPCs in response to PTH.…”
Section: Impact Of Intrinsic and Extrinsic Factors On The Osteo-hematmentioning
confidence: 99%
“…At the same time, there is evidence of qualitative differences in hematopoiesis that is supported by stroma derived from different ontological environments. 17,18 In an hUCBDSC nude mouse transplantation study, we reported that by providing a cord blood-associated environment, we achieved higher concentrations and faster recovery of circulating platelets in the PB, suggesting that transplantation of hUCBDSCs qualitatively promotes megakaryocytopoiesis.…”
Section: Resultsmentioning
confidence: 93%